Characterization, Delignification And Hydrolysis Of Malaysian Elephant Grass For The Recovery Of Sugar - Shahifulnaas, Muhammad Aiman (Universiti Sains Malaysia, 2017)
T he price rising of crude oil and the depreciation of worldwide fossil fuel reserves become one of the toughest obstacle that must be confronted in this modern era plus with the alarming of unavoidable global warming that gives an awful impact to the environment due to increase in utilization of petroleum. However, to guarantee of environmental protection and energy security, the search of alternative energy is essential. Lignocellulosic are promising raw materials for sugar production since they are abundant renewable resources and its non-food status that not compete with food production. Malaysian elephant grass (Pennisetum purpureum, Schumach.) (USM Herbarium 11741) also known as Napier grass is one of a lignocellulosic material that has tremendous potential for carbohydrate polymers production in tropical countries like Malaysia due to their adaptability and availability. In this study, the physical characteristics of the grass were first determined by using SEM and examined the surface morphology before and after the process of delignification. It shows that the surface morphology has smooth, compact and homogeneous structure. Next, the efficiency of alkaline and acidic pretreatments was determined by compared NaOH solution and H2SO4 solution. 10g of the sample with size 1 cm x 1 cm is soaked with 1 M of solution and heated at 70˚C in 2 hours. It shows that NaOH solution has better efficiency compare to H2SO4 solution with 60.87% weight loss. All parameters (concentration, solid to liquid ratio and temperature) are being tested to determine whether it effect sugar recovery. It shows that all parameters are affect sugar recovery.